Helping Children with Homework - Heidi Liss Radunovich (EDIS)
“Although children and their parents often dread homework, it provides an important opportunity for children to practice what they have learned in school, get more in-depth information, apply skills learned more broadly, obtain important learning and organizational skills, and learn how to work independently with self-discipline. Homework can also give parents a sense of what their children are doing in school and how well they are doing. And homework can even enhance parents’ relationships with their children.” This 2-page Family Album Radio transcript was written by Heidi Liss Radunovich, and published by the UF Department of Family, Youth and Community Sciences, March 2012.